Health Status of Coral Reef in Tunda Island, Banten Province, Indonesia - Mujiyanto Mujiyanto; Mheda G. Garcia; Joni Haryadi; Risnawati Rahayu; R. Arif Budikusuma (Marine Science Department Diponegoro University, 2020)
Coral reef is an important underwater ecosystem supporting people’s lives in coastal areas. One of the communities depending on the coral reef ecosystem for its food, livelihood, shoreline protection, and recreation needs is a community in Tunda Island. This research aims to analyze and determine the health status of coral reef in the island using a survey method. It was conducted in July 2018 and July 2019. Underwater photography transects were established at two depth areas of ± 3-4 m (shallow water) and ± 10-11 m (reef slope). Analysis of the results of live coral cover was divided into eight categories of groups based on CPCe output series 4.1. The values of coral reef cover at first depth (± 3-4 m) were 64.86% (east side of the island), 55.76% (north toward east side), and 32.22% (west side). The values of coral reef cover at second depth (± 10-11 m) were 36.36%, 25.00%, and 23.63% on the north toward east, east, and central north sides of the island, respectively. In shallow waters of Tunda Island, the coral reef health is classified as moderate to good, mostly those located on the east and the north toward the east sides. At reef slope, the coral reef health is classified as damaged to poor, particularly those located on the south and the south toward the west sides. The difference in the health values implies that most corals occur in shallow waters while deep corals differ from those near the surface and are not safe from impacts of the activities in the coastal area of Tunda Island.